Toxicity of silver, lead an nanoplastics to early life stages of amphibians - Brotas, David Manuel Branco (2019)
Over the last 40 years amphibian populations are reported to be increasingly declining each year with amphibian species disappearing completely from their natural place of occurrence. This decline is mostly due to anthropogenic disturbances and the negative effects they pose to this group of vertebrates. Amphibians are considered very sensitive to environmental changes, namely because they are characterized by a highly permeable skin. Until recently, the risk assessment of chemicals for amphibians was based on the data generated for fish (for aquatic life stages) and for birds and mammals (for terrestrial life stages). However, it has been reported that the use of data from these three groups of vertebrates may underestimate the risk of some chemicals to amphibians. It is, therefore needed to generate toxicity data specifically for amphibians in order to promote its accurate protection and conservation. The present study aimed at assessing the toxicity of two metals and a nanoplastic to aquatic early life stages of an amphibian species. It also intended to assess the adequacy of using in vitro assays, with amphibian cell lines, as surrogates of the in vivo assays to assess the toxicity of the selected chemicals to this group of organisms. To attain these objectives the anuran Xenopus laevis was used as test model species. Embryos and tadpoles of X. laevis were exposed to a set of concentrations of silver, lead or nanoplastics of polystyrene and the following endpoints were monitored: for embryos – mortality, malformations, hatching rate and body length; and for tadpoles – mortality, growth rate (as weight gain and body length increase), developmental stage, and heart beat rate. Lead concentrations equal or above 0.22 mg/L induced significant adverse effects in the hatching rate and snout-to-vent length of larvae exposed to lead since the embryonic stage. Tadpoles exposed to concentrations of lead equal or above 0.49 mg/L showed significant changes in the weight gain and total body growth rate. The in vitro assays with lead revealed a significant reduction of cells viability at concentrations equal or higher than 0.078 mg/L. Regarding silver, concentrations as low as 0.013mg/L induced the appearance of malformations, an early hatching and increased snout-to-vent length of larvae. This same concentration induced an increase in the tail and total body growth rates. The in vitro assay revealed to be very sensitive to silver, concentrations as low as 0.0004 mg/L of silver affected negatively the viability of cells. Nanoparticles of polystyrene induced no significant effects on both embryos and tadpoles. Overall, the embryos and tadpoles of X. laevis exhibited a similar sensitivity to the tested chemicals. The in vitro assays performed with lead, revealed that A6 cell lines are slightly more sensitive to lead than embryos or tadpoles of X. laevis. In the case of silver, toxic effects in the cell lines were observed at concentrations much lower than those inducing effects in embryos and tadpoles. The obtained results suggest that for early stages of risk assessment frameworks, in vitro assays may be used for a first toxicity screening in order to avoid running animal experimentation.